Molecular phylogeny of Malaysian groupers inferred from mitochondrial (Cytochrome b) and nuclear (Tmo-4c4 and Rag-1) genes - Nor Rahim, Nor Syakina (2017)
Groupers are known as one of the important marine and estuarine fishes. They are widely distributed in tropical and subtropical open waters. Difficulty in netting them in wild has increased their demand in the market thus resulting in overexploitation of these fishes. The classification also difficult for most species from this family due to their homology characteristics which is most notably among closely related species which makes the conservation and management of these fishes ambiguous. This study aimed to elucidate the phylogenetic relationship of wild grouper in Peninsular Malaysia. Sample collection was done for nine sites which are from Terengganu (N=24), Kelantan (N=6), Perak (N=9), Pahang (N=10), Perlis (N=1), Perlis (N=1), Kedah (N=5), Selangor (N=26), Pahang (N=10), Malacca (N=3) and Johor (N=2) coastal areas. Samples were identified based on their morphological characteristics. Molecular phylogeny study was done inferred using Mitochondrial Cytochrome b (Cyt b), Nuclear Tmo-4c4 and Recombination activating gene-1 (Rag-1) genes and combined Mitochondrial and Nuclear genes. The results revealed a total 86 individuals belonging to 12 species representing three genera which are Epinephelus, Cephalopholis and Plectropomus. The phylogenetic trees were contructed for Neighbour-Joining (NJ), Maximum Parsimony (MP), Maximum Likelihood (ML), Minimum Evolution (ME), and Bayesian Inference (BI) which were implemented by Molecular Evolution Genetic Analysis 7.01 (MEGA) and MrBayes 3.2.1. One consistent result across all the analyses was the monophyletic status of the subfamily of Epinephelinae. It is revealed that genus Plectropomus sister to the rest genera. Genus Epinephelus was clustered into two clades which is constant for all analyses. The separation confidence level between cluster Epinephelus, Cephalopolis and Plectropomus were 100% respectively for BI analysis based on combined dataset. Molecular data revealed that combined dataset helps increases the phylogenetic resolution compared to single gene phylogeny where the dataset well resolved the deeper node within genus Epinephelus compared to single gene analyses. Nevertheless, several genetic relationships remain unresolved particularly among morphologically similar species, for instance between Epinephelus fario and E. longispinis and species with limited number of individuals which is E. coioides. This study have aids in giving baseline information regarding groupers particularly in Malaysia which related to the area of taxonomy, phylogeny and genetic diversity which are important for their appropriate sustainable management, for conservation as well as aquaculture purposes.